2022
DOI: 10.1080/0886022x.2022.2110894
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil-to-lymphocyte ratio may indicate when to start hemodialysis

Abstract: We evaluated whether the neutrophil-to-lymphocyte ratio (NLR) could aid dialysis decision-making in combination with the clinical presentation and biochemical findings. We retrospectively evaluated the medical records of 279 patients who commenced chronic maintenance hemodialysis. We compared the laboratory findings at 6 months before dialysis to those at dialysis initiation. NLR cutoffs and risk factors for each of six uremic symptoms were determined. Mean age was 60.7 years and mean estimated glomerular filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“… 27 There is also evidence that the NLR could serve as a supplementary marker for predicting the onset of uremic symptoms and the need for hemodialysis in patients with CKD5. 28 Chen et al reported that an elevated NLR was associated with longer hospital stay and more dialysis sessions. 29 Other studies of hemodialysis patients concluded that the NLR was a predictor of mortality and cardiovascular events in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“… 27 There is also evidence that the NLR could serve as a supplementary marker for predicting the onset of uremic symptoms and the need for hemodialysis in patients with CKD5. 28 Chen et al reported that an elevated NLR was associated with longer hospital stay and more dialysis sessions. 29 Other studies of hemodialysis patients concluded that the NLR was a predictor of mortality and cardiovascular events in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the neutrophil-to-lymphocyte ratio (NLR) was proposed as a supplementary marker of CKD progression and the need for starting hemodialysis [16,39,40]. Even in the patients with normal white blood cell count, higher NLR was associated with higher long-term all-cause mortality in CKD stage 5 [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior to HD initiation a higher NLR may be associated with the severity of chronic kidney disease and mineral bone disease. Therefore, the NLR can be used to predict uremic symptoms and the need for HD in patients with chronic kidney disease [ 53 ]. These results enhance our understanding of the association between the NLR and quality of life in individuals undergoing dialysis.…”
Section: Nlr and Hdmentioning
confidence: 99%